THE USE OF CONFLICT IN CRITICAL READING PRACTICES: ESL STUDENTS’ OPINIONS ON THE EFFECTIVENESS OF THE CRITICAL READING MODULE - Suyansah Swanto; Wardatul Akmam Din; Irma Wani Othman; Megawati Soekarno (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Critical reading is regarded by many as the most important of the four skills, and the desire to enhance the ability of ESL students to read critically is grounded in the knowledge that increased capability will give them an extra advantage in not only extracting valuable information from texts and acquiring knowledge but also in using it more effectively in their academic assignments. Therefore, it is necessary to carefully consider how to develop a module aimed at such outcomes, and this paper reports on a study that examines the opinions of a group of Malaysian undergraduate students at a Malaysian University with regard to their experience with the Critical Reading Module and to highlight the development of these ESL readers. Data for this paper was collected from a questionnaire distributed at two phases (week 1 and week 14) to sixty undergraduate students. The findings show that at the start of the research this group of Malaysian students demonstrated a lack of analytic skill. However, post-research they did show increased confidence as readers and they became more critical in their reading.